2006
DOI: 10.1620/tjem.210.169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Perfusion in Eyes and Cerebral Perfusion Defects in a Patient with Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is known as the most common form of inherited mental retardation. In our study, brain perfusion single photon emission computed tomography (SPECT) was performed in a 6 year-old boy diagnosed with FXS. Diffuse bilateral uptake of Technetium-99m hexamethyl propylene amine oxime (99mTc-HMPAO) was noted in his orbits, as well as cortical perfusion defects (hypoperfusion in the right parietal and the left temporal lobe). Ophthalmologic examination showed no pathological findings. Magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…In exploring FXS abnormalities, studies in a mouse model of the syndrome have demonstrated increased neocortical blood vasculature (Galvan and Galvez, ). These findings are consistent with reports from FXS patients demonstrating abnormal cerebral blood profusion (Balci et al, ; Kabakus et al, ) and suggest abnormal vascular development in FXS. One of the most prominent regulators of vascular growth, with increased expression being synonymous with increased vasculature, is VEGF‐A (Vasculature Endothelial Growth Factor A) (Neufeld et al, ).…”
Section: Introductionsupporting
confidence: 92%
“…In exploring FXS abnormalities, studies in a mouse model of the syndrome have demonstrated increased neocortical blood vasculature (Galvan and Galvez, ). These findings are consistent with reports from FXS patients demonstrating abnormal cerebral blood profusion (Balci et al, ; Kabakus et al, ) and suggest abnormal vascular development in FXS. One of the most prominent regulators of vascular growth, with increased expression being synonymous with increased vasculature, is VEGF‐A (Vasculature Endothelial Growth Factor A) (Neufeld et al, ).…”
Section: Introductionsupporting
confidence: 92%